Nature-Based Solutions Mainstreaming: Challenges and Opportunities for Climate-Related Natural Hazards Mitigation in Western Balkans Countries - Marijana Kapović Solomun; Saša Eremija; Igor Bogunović; Artan Hysa; Goran Češljar; Ilija Čigoja; Carla S.S. Ferreira (South-East European Forestry, 2025)
Nature-based solutions (NbS) provide a unique opportunity to address sustainable development challenges and supply benefits for both people and nature, such as support for climate change mitigation. This study compiles information about the most common climate-related natural hazards in the Western Balkans (WB) region. It assesses the institutional, policy, and legal framework for implementing NbS to address these problems. The study compares the policies, knowledge gaps, and current challenges to NbS mainstreaming in Croatia, a European Union (EU) country, with those in Bosnia and Herzegovina, Serbia, and Albania as non-EU countries. In EU countries, the policy framework transposes the main European Directives, which enforce the need to implement NbS, climate change, and natural hazards mitigation, mainly focused on built infrastructure or technical measures in non-EU countries. The possibilities to mainstream NbS, such as the need for a centralized governance structure, using NbS to integrate different sectoral policies, and the involvement of stakeholders and funding agencies, are discussed. The WB region must advance NbS implementation for climate change adaptation, disaster risk reduction, and other pressing societal challenges. The institutional structure and policy framework relevant to implementing NbS to mitigate climate-related natural hazards show similarities between the WB countries. However, significant differences, particularly regarding transposition of EU Directives between the EU and non-EU WB countries, are easily recognizable.